2011
DOI: 10.3727/096368910x550170
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Combination of a JNK Inhibitor and Simvastatin Protects Porcine Islets from Peritransplant Apoptosis and Inflammation

Abstract: Intraductal administration of a c-Jun NH(2)-terminal kinase (JNK) inhibitor enhances islet viability. However, its role in reducing the inflammatory response in islets is unknown. It is also unknown whether a JNK inhibitor could act in synergy with statins. We examined if the sequential combination of a JNK inhibitor and simvastatin would reduce islet inflammation and improve islet viability. We performed porcine islet isolation with or without intraductal administration of SP600125, a JNK inhibitor. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…The surgical procedure was performed identically throughout the study period and is described elsewhere (12,13). After transportation, islet isolation was performed using the modified Ricordi method that has been previously described (13).…”
Section: Pig Islet Isolationmentioning
confidence: 99%
“…The surgical procedure was performed identically throughout the study period and is described elsewhere (12,13). After transportation, islet isolation was performed using the modified Ricordi method that has been previously described (13).…”
Section: Pig Islet Isolationmentioning
confidence: 99%
“…Moreover, the excessive activation of JNK in peripheral insulin-sensitive tissues promotes IR [ 67 ]. It was demonstrated that inhibiting JNK reduced the release of IR-related proinflammatory cytokines such as TNF- α and MCP-1 [ 68 70 ]. Interestingly, JNK-1 deficiency in adipose tissue protects against hepatic steatosis and promotes glucose intolerance, insulin clearance, IR, and hepatic steatosis.…”
Section: Signaling Pathways Linking Inflammation To Insulin Resistmentioning
confidence: 99%
“…The use of JNK inhibitor SP600125 in combination with nicotinamide and simvastatin protected porcine islets from peritransplant inflammation and apoptosis. Intraductal administration of JNK inhibitor protected islets by inhibiting the production of proinflammatory cytokines IL-1 β , TNF- α , IFN- γ , IL-6, IL-8, and MCP-1 in vivo [145]. …”
Section: Anti-inflammatory Strategies To Improve Islet Transplantamentioning
confidence: 99%